PENDIDIKAN PERDAMAIAN DAN FENOMENA KEKERASAN KULTURAL PADA ANAK DAN REMAJA DI INDONESIA - Frisca Alexandra (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The phenomenon of cultural violence involving children and adolescents in Indonesia shows an increasing number from year to year. This causes cases in the world of education to be in the top four after cybercrime and pornography. The phenomenon of cultural violence was born because so far the education system in Indonesia has only focused on the transfer of knowledge while aspects of character development and the cultivation of moral values have received minimal attention. The Indonesian government itself realizes the importance of overcoming the problem of cultural violence in children and adolescents, the government then issued Minister of Education and Culture Regulation No. 82 of 2015. However until 2018, the number of cases of cultural violence in children and adolescents is still very high. There is another approach that can be taken to complement existing efforts, namely through peace education. The main goal of peace education is to create and increase tolerance in children and adolescents. Keywords: peace education, cultural violence, children and adolescents